On the Stabilization of Chaotic Systems based on Synchronization Technique - Kamel, Guesmi; Baghdadi, Hamidouche; Najib, Essounbouli (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we present a new method for nonlinear control and stabilization of chaos based on the synchronization technique. The idea behind this is to synchronize the slave chaotic system with a master stable system. The stability proof is carried out using the linearization method. Two cases of continuous and discrete systems are considered and the synchronization for stabilization is made between identical and different systems. Theoretical proofs and numerical simulations are given to demonstrate the efficiency of the proposed approach.